Pharmacogenomic study of heart failure and candesartan response from the CHARM programme. (23rd June 2022) - Dubé, Marie‐Pierre; Chazara, Olympe; Lemaçon, Audrey; Asselin, Géraldine; Provost, Sylvie; Barhdadi, Amina; Lemieux Perreault, Louis‐Philippe; Mongrain, Ian; Wang, Quanli; Carss, Keren; Paul, Dirk S.; Cunningham, Jonathan W.; et al.
Abstract: Aims: The Candesartan in Heart failure Assessment of Reduction in Mortality and morbidity (CHARM) programme consisted of three parallel, randomized, double‐blind clinical trials comparing candesartan with placebo in patients with heart failure (HF) categorized according to left ventricular ejection fraction and tolerability to an angiotensin‐converting enzyme inhibitor. We conducted a pharmacogenomic study of the CHARM trials with the objective of identifying genetic predictors of HF progression and of the efficacy and safety of treatment with candesartan. Methods: We performed genome‐wide association studies in 2727 patients of European ancestry from CHARM‐Overall and stratified by CHARM study according to preserved and reduced ejection fraction and according to assignment to the interventional treatment with candesartan. We tested genetic association with the composite endpoint of cardiovascular death or hospitalization for heart failure for drug efficacy in candesartan‐treated patients and for HF progression using patients from both candesartan and placebo arms. The safety endpoints for response to candesartan were hyperkalaemia, renal dysfunction, hypotension, and change in systolic blood pressure between baseline and 6 weeks of treatment. To support our observations, we conducted a genome‐wide gene‐level collapsing analysis from whole‐exome sequencing data with the composite cardiovascular endpoint. Results: We found that the A allele (14% allele frequency) of the genetic variant rs66886237 at 8p21.3 near the gene GFRA2 was associated with the composite cardiovascular endpoint in 1029 HF patients with preserved ejection fraction from the CHARM‐Preserved study (hazard ratio: 1.91, 95% confidence interval: 1.55–2.35; P = 1.7 × 10 −9 ). The association was independent of candesartan treatment, and the genetic variant was not associated with the cardiovascular endpoint in patients with reduced ejection fraction. None of the genome‐wide association studies for candesartan safety or efficacy conducted in patients treated with candesartan passed the significance threshold. We found no significant association from the gene‐level collapsing analysis. Conclusions: We have identified a candidate genetic variant potentially predictive of the progression of heart failure in patients with preserved ejection fraction. The findings require further replication, and we cannot exclude the possibility that the results may be chance findings.